The paradox of moral cleansing: When physical cleansing leads to increased contamination concerns. (December 2018) - Gilchrist, Philippe T.; Schnall, Simone
Abstract: Background and objectives: Moral threats, including threats to moral self-worth, have been associated with contamination concerns. Paradoxically, although self-cleansing provides temporary relief, it can worsen feelings of contamination. Self-affirmation might be an effective strategy, especially following obsessive type cognitions (e.g., responsibility beliefs) when moral threats are reactivated. Methods: In Experiment 1, participants recalled an immoral deed and then self-cleansed (using a hand-wipe), completed a control task, or self-affirmed. Contamination concerns were subsequently measured by a washing task. In Experiment 2, the same procedure was used but obsessive-type cognitions were activated by asking participants a series of questions about obsessive beliefs. Results: As expected, relative to the control condition, both self-affirmation and self-cleansing resulted in less subsequent repeated washing behaviour in Experiment 1. In Experiment 2, when the immoral recall was followed by activation of obsessive-type cognitions, self-cleansing led to more guilt and repeated washing than self-affirmation and control. Rather than alleviating feelings of contamination, physical self-cleansing led to more contamination concerns and guilt when in the context of activated obsessive-type cognitions, possibly because it paradoxically makes (moral) cleanliness goals salient. Limitations: Future research needs to test clinical populations, for whom contamination concerns are all the more central. Conclusions: This research provides further evidence of the influence of moral threat in contamination concerns, and the limits of moral cleansing. Self-affirmation resulted in less contamination concerns under both a neutral condition and activated obsessive type cognitions. Highlights: Self-affirmation and self-cleansing reduce contamination concerns following guilt. Following obsessive-type cognitions, self-cleansing raises contamination concerns. Results highlight the potential for detrimental effects of moral self-cleansing.